1985
DOI: 10.1021/ac00285a042
|View full text |Cite
|
Sign up to set email alerts
|

Thermal lens measurements of optical computation of the laser beam spot size

Abstract: A signal processor, which computes the second spatial moment or spot size of a laser beam In two dimensions by optical rather than electronic means, reduces the Impact of spatial noise on thermal lens measurements. The spot size determination Is sufficiently fast to allow time averaging by either transient recording or lock-in amplification; the ultimate speed of computation Is limited only by the transit time of light through the device. The thermal lens detection limits using the optical processor are A m,n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Using an approach based on the diffraction theory of Sheldon et al, 44 Carter and Harris successfully predicted absolute values of the thermal lens response. 46 In order to achieve accuracy, the aberrant nature of the photoinduced lens was taken into account.…”
Section: U(t)mentioning
confidence: 99%
“…Using an approach based on the diffraction theory of Sheldon et al, 44 Carter and Harris successfully predicted absolute values of the thermal lens response. 46 In order to achieve accuracy, the aberrant nature of the photoinduced lens was taken into account.…”
Section: U(t)mentioning
confidence: 99%
“…This dot product can be calculated either explicitly by MDCs or implicitly MOCs. In previous applications of MOC, the ILS/LD model was either implicitly assumed or explicitly applied [1,[9][10][11][12].…”
Section: Implementation Of Generalized Multivariate Optical Computatimentioning
confidence: 99%
“…For example, Caulfield and Mueller employed a linear variable filter for predictive classification of colored glasses [9]. In 1985, Jansen and Harris employed optical computations to calculate the two-dimensional second moment of a laser beam waste to determine focus diameter during thermal lens experiments [10]. More recently Lewis et al employed optical computations for edge finding in chemical images [11] and Prakash et al demonstrated the advantages of optical computations for multivariate calibration of rhodomine dye mixtures [1].…”
Section: Introductionmentioning
confidence: 99%
“…sample) and is centered on a mask having a radially-symmetric, parabolic transmittance profile; the intensity of radiation transmitted by this mask, collected with a plano-convex lens and focused onto a photomultiplier, is proportional to the second spatial moment of the probe beam intensity distribution. 35 Changes in the far-field area of the beam caused by the thermal lens are thus detected using information from the entire probe beam and not just the center intensity; this approach reduces the impact of spatial noise on the measurement and improves the precision of the signal by 1 order of magnitude over measuring the beamcenter intensity.…”
Section: Introductionmentioning
confidence: 99%